PALEOMAGNETISM OF A LATE CRETACEOUS ISLAND ARC COMPLEX FROM SOUTH SAKHALIN, EAST ASIA: CONVERGENT BOUNDARIES FAR AWAY FROM THE ASIAN CONTINENTAL MARGIN? - Bazhenov M.L.; Levashova N.M.; Bragin N.Y.; Fedorov P.I.; Bragina L.G.; Lyapunov S.M.; Zharov A.E.; Kodama K. (My University, 2001)
The Hokkaido-Sakhalin fold system stretches for ~˜1500 km along the eastern coast of Asia and consists of several N-S trending tectonic belts. Studies in South Sakhalin show that the northern part of the Tonino-Aniva Peninsula (Ozersk unit) is a counterpart of the Tokoro belt on Hokkaido, Japan. In the eastern part of the Ozersk unit, 195 hand samples were sampled at 20 sites from Campanian-Maastrichtian tuffaceous siltstones and sandstones of the Chayka Formation of island arc affinity. Stepwise thermal demagnetization isolates a postfolding low- to intermediate-temperature component (B) of normal polarity. A high-temperature component (A) is isolated from about half the samples. Because of strong overlap of unblocking temperature spectra of these two components in other samples, direct observations and remagnetization circles were combined for calculation of site-mean directions. Component A is mostly of reversed polarity; a few samples of normal polarity are found at three sites. The presence of two polarities with approximately antipodal directions and the positive fold test imply a prefolding, and most probably primary, origin of component A. A formation-mean inclination of 45.0°±6.4° calculated with the aid of inclination-only statistics corresponds to a latitude of 26.6°±5.2°N. A similar inclination is derived from a late Cretaceous island arc complex from the Tokoro belt on Hokkaido. Since both mean inclinations are ˜30° lower than the coeval Eurasian reference value, a large-scale northward transport of the entire Tokoro island arc is inferred. We exclude the possibility of displacement with the Kula plate and coast-parallel transport; instead, intra-oceanic motion with the Pacific plate and docking at the Eurasian margin at circa 30 Ma are inferred. Combined paleomagnetic data from the Tokoro belt, the Nemuro belt and Kamchatka region imply that a system of intra-oceanic island arcs existed in the northwest Pacific in Late Cretaceous time.
Keywords: Cretaceous; Hokkaido-Sakhalin fold system; Мезозой::Меловая; Mesozoic::Cretaceous